Comparative study of the protein profiles of Sunki mandarin and Rangpur lime plants in response to water deficit - Oliveira, Tahise M.; da Silva, Fernanda R.; Bonatto, Diego; Neves, Diana M.; Morillon, Raphael; Maserti, Bianca E.; Coelho Filho, Mauricio A.; Costa, Marcio G. C.; Pirovani, Carlos P.; Gesteira, Abelmon S. (2017)
Background: Rootstocks play a major role in the tolerance of citrus plants to water deficit by controlling and adjusting the water supply to meet the transpiration demand of the shoots. Alterations in protein abundance in citrus roots are crucial for plant adaptation to water deficit. We performed two-dimensional electrophoresis (2-DE) separation followed by LC/MS/MS to assess the proteome responses of the roots of two citrus rootstocks, Rangpur lime (Citrus limonia Osbeck) and ‘Sunki Maravilha’ (Citrus sunki) mandarin, which show contrasting tolerances to water deficits at the physiological and molecular levels. Results: Changes in the abundance of 36 and 38 proteins in Rangpur lime and ‘Sunki Maravilha’ mandarin, respectively, were observed via LC/MS/MS in response to water deficit. Multivariate principal component analysis (PCA) of the data revealed major changes in the protein profile of ‘Sunki Maravilha’ in response to water deficit. Additionally, proteomics and systems biology analyses allowed for the general elucidation of the major mechanisms associated with the differential responses to water deficit of both varieties. The defense mechanisms of Rangpur lime included changes in the metabolism of carbohydrates and amino acids as well as in the activation of reactive oxygen species (ROS) detoxification and in the levels of proteins involved in water stress defense. In contrast, the adaptation of ‘Sunki Maravilha’ to stress was aided by the activation of DNA repair and processing proteins. Conclusions: Our study reveals that the levels of a number of proteins involved in various cellular pathways are affected during water deficit in the roots of citrus plants. The results show that acclimatization to water deficit involves specific responses in Rangpur lime and ‘Sunki Maravilha’ mandarin. This study provides insights into the effects of drought on the abundance of proteins in the roots of two varieties of citrus rootstocks. In addition, this work allows for a better understanding of the molecular basis of the response to water deficit in citrus. Further analysis is needed to elucidate the behaviors of the key target proteins involved in this response.